2022
DOI: 10.1101/2022.09.07.507024
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

N-terminal cardiac myosin-binding protein C interactions with myosin and actin filaments using time-resolved FRET

Abstract: Myosin binding protein-C (cMyBP-C) is a sarcomeric protein responsible for normal contraction and relaxation of the heart. We have used time-resolved fluorescence resonance energy transfer (TR-FRET) to resolve the interactions of cardiac myosin and F-actin with cMyBP-C, focusing on the N-terminal region. The results imply roles of these bound protein complexes in myocardial contraction, with particular relevance to β-adrenergic signaling, heart failure and hypertrophic cardiomyopathy (HCM). N-terminal cMyBP-C … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…The THB is a specific motif for the cardiac isoform of MYBP-C, providing the platform for potential binding to actin and myosin [46]. In vitro studies have shown that the mutations in THB can alter these interactions [47]. Further evidence for the causality of the p.R346H variant was obtained by our family studies.…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…The THB is a specific motif for the cardiac isoform of MYBP-C, providing the platform for potential binding to actin and myosin [46]. In vitro studies have shown that the mutations in THB can alter these interactions [47]. Further evidence for the causality of the p.R346H variant was obtained by our family studies.…”
Section: Discussionmentioning
confidence: 56%
“…There were no homozygous or compound heterozygous patients with two truncating variants (Figure 1). Compared to patients with a single P/LP/VUS-LP variant (n = 70), patients with two rare variants (n = 10) had a significantly higher SCD risk score (5.9 [3.5-7.3] vs. 2.9 [1.9-4.0], p = 0.011), larger left atrium (52 [43][44][45][46][47][48][49][50][51][52][53][54][55][56][57] vs. 43 [39][40][41][42][43][44][45][46][47][48][49][50] mm, p = 0.017), more frequent high systolic pulmonary artery pressure (63 vs. 14%, p = 0.004), and a trend toward more frequent severe NYHA class III/IV (38 vs. 11%, p = 0.07). The clinical course of HCM was highly variable, ranging from mild symptoms to severe HF progression and SCD in middle age.…”
Section: • Multiple Variantsmentioning
confidence: 99%